Radiographic atlas of skeletal maturation - Kahn, S. Lowell (New York, NY : Thieme, 2012)
"Despite the advent of modern cross-sectional imaging, skeletal radiographs remain at the crux of the initial diagnosis, particularly in the emergency and outpatient settings. The images contained herein represent composite individuals obtained at three-month intervals for the first two years of life and at yearly intervals thereafter. The authors provide a comprehensive set of reference images that document the progressive skeletal development, demonstrating the configuration, density, and relative size of the various body parts for males and females. Given the broad application of radiographs in the clinical setting, this atlas is not only intended for practicing and training radiologists, but for all of those who employ radiographs as part of their practice"--Provided by publisher.
Section I. Male -- section II. Female.
Includes bibliographical references.
WorldCat record variable field(s) change: 650
Keywords: Bones -- Growth -- Atlases; Bones -- Radiography -- Atlases; Radiography; Bone Development; Bone and Bones -- diagnostic imaging; Radiography; Os -- Croissance -- Atlas; Os -- Radiographie -- Atlas; Radiographie; HEALTH & FITNESS -- Diseases -- Musculoskeletal; MEDICAL -- Orthopedics; MEDICAL -- Rheumatology; Bones -- Growth; Bones -- Radiography; Atlas; atlases; Scientific atlases; Atlases; Atlas